2011
DOI: 10.1111/j.1095-8649.2011.03065.x
|View full text |Cite
|
Sign up to set email alerts
|

Environmental factors influencing adult sex ratio in Poecilia reticulata: laboratory experiments

Abstract: The potential causes of adult sex ratio variation in guppies Poecilia reticulata were tested in laboratory experiments that evaluated the mortality rates of male and female P. reticulata exposed to potential predators (Hart's rivulus Rivulus hartii and freshwater prawns Macrobrachium crenulatum) and to different resource levels. Poecilia reticulata mortality increased in the presence of R. hartii and M. crenulatum, and low resource levels had an effect on mortality only in the presence of M. crenulatum. Rivulu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…Even if all migrants were male, this level of migration would shift a sex ratio of 0.5 to just 0.475, thus mortality is likely much more important than migration. Others (Seghers and McKellar et al ) have suggested that males are more vulnerable to predators, especially R. hartii , and that this is key in explaining female‐biased sex ratios because this predator preferentially feeds on male guppies in the laboratory (McKellar and Hendry ). Predation likely contributes to male mortality but cannot explain why temporal variation in adult sex ratio is correlated among our populations.…”
Section: Discussionmentioning
confidence: 99%
“…Even if all migrants were male, this level of migration would shift a sex ratio of 0.5 to just 0.475, thus mortality is likely much more important than migration. Others (Seghers and McKellar et al ) have suggested that males are more vulnerable to predators, especially R. hartii , and that this is key in explaining female‐biased sex ratios because this predator preferentially feeds on male guppies in the laboratory (McKellar and Hendry ). Predation likely contributes to male mortality but cannot explain why temporal variation in adult sex ratio is correlated among our populations.…”
Section: Discussionmentioning
confidence: 99%
“…Male guppies appear to be more sensitive to high temperatures than females; thus, temperature differences between sites are expected to impact upon the ASR (Pettersson et al ., ). In addition, with males being more colourful and active than females, the males are predated more often than the females by one predator (killifish Rivulus hartii ) but not by another (freshwater prawn Macrobrachium crenulatum ; McKellar & Hendry, ). Therefore, variation in predator densities between streams may also contribute to ASR variation (McKellar & Hendry, ).…”
Section: Spatial and Temporal Variation In Adult Sex Ratiosmentioning
confidence: 99%
“…Concerning sex differences in vulnerability to predators, mixed results were found. In a laboratory study, male guppies suffered higher mortality rates from a piscine predator (McKellar & Hendry 2011). However, a recent mark and recapture study has suggested that the female-biased sex ratio commonly observed in natural populations is unlikely to be explained by a greater male vulnerability to predators but rather by environmental factors such as seasonal variability in resources (Arendt et al 2014).…”
Section: Introductionmentioning
confidence: 96%